Protecting Brazil's tropical forest: a CGE analysis of macroeconomic, sectoral, and regional policies - Manfred Wiebelt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
The 'deforestation problem' in Brazil consists of a variety of interrelated issues, of which this paper identifies a regional, sectoral and macroeconomic dimension. Using a regionally and sectorally disaggregated general equilibrium model of Brazil, it is shown that macroeconomic reform is complementary to conservation policies. Therefore, if not for other reasons, macroeconomic reform is urgently needed to provide an adequate framework for microeconomic conservation policies to be effective. The analysis also shows that regional land taxes in the Amazon outperform the reduction of fiscal incentives for agriculture, both with regards to ecological effectiveness and efficiency. Finally, the results do not support claims for compensation payments.
Keywords: Q2; Q28; C68; 330; deforestation; public policy; general equilibrium analysis; Brazil; Abholzung; Wirtschaftspolitische Wirkungsanalyse; Allgemeines Gleichgewicht; Tropen; Brasilien